Characterization of the mitochondrial genomes of three species in the ectomycorrhizal genus Cantharellus and phylogeny of Agaricomycetes - Li, Qiang; Liao, Min; Yang, Mei; Xiong, Chuan; Jin, Xin; Chen, Zuqin; Huang, Wenli (International journal of biological macromolecules, 2018)
Cantharellus is a large ectomycorrhizal genus. Here, we assembled and annotated the mitochondrial genomes of C. lutescens, C. appalachiensis, and two specimens of C. cibarius. We found that all four mitochondrial genomes were circular and between 56,786 bp and 80,736 bp, long. The length and GC content of the protein-coding genes (PCGs) in the four mitogenomes varied. All tRNAs were folded into classical cloverleaf secondary structures; 16 of the 26 identified tRNAs contained variable sites across Cantharellus genus. C. appalachiensis was found containing the most repeated sequences (11.32% of the mitogenome), along with a substantial number of gene rearrangements. Comparative analysis of three C. cibarius specimens indicated that the mitogenomes of specimens from different regions differed. The Ka/Ks ratios of all 15 PCGs identified across all four mitogenomes were <1, indicating that these genes have been subject to purifying selection. Phylogenetic analysis recovered a well-supported tree based on a combined analysis of the 15 PCGs. In addition, we identified cob, cox1, and rnl as potential single-gene markers for the analysis of phylogenetic relationships among Agaricomycetes species. The mitogenomes reported in this study will facilitate the study of population genetics and evolution in Cantharellus and other closely related species.